2017
DOI: 10.3390/app7111121
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Noise Reduction by Earmuffs with Coir and Coir/Carbon Fibre-Reinforced Polypropylene Ear Cups

Abstract: Natural fibres have been extensively studied due to their potential in a wide range of applications. This study aims to demonstrate the viability of composite earmuffs for low-frequency noise reduction in continuous and transient noise environments. Pink noise and aircraft take-off exterior noise were considered for the former and the latter, respectively. The assembly components of the composite earmuffs were kept identical to a commercial earmuff, which served as a reference for results comparison. Based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In their case, the cavity resonance occurred at around 4.0-4.5 kHz. Based on the above understanding, it is highly possible that the IL dip at around 100-200 Hz was attributed to the pumping motion of the ear cups, which is dependent on the design parameters and the leakages around the cushion pads [30]. Boyer et al [6] revealed that the pumping motion of the ear cups would highly influence the acoustical performance of the earmuff at low frequency.…”
Section: Acoustical Performance Of the Composite Earmuffs In Pinkmentioning
confidence: 99%
“…In their case, the cavity resonance occurred at around 4.0-4.5 kHz. Based on the above understanding, it is highly possible that the IL dip at around 100-200 Hz was attributed to the pumping motion of the ear cups, which is dependent on the design parameters and the leakages around the cushion pads [30]. Boyer et al [6] revealed that the pumping motion of the ear cups would highly influence the acoustical performance of the earmuff at low frequency.…”
Section: Acoustical Performance Of the Composite Earmuffs In Pinkmentioning
confidence: 99%
“…Secondly, the clunking noises are found in low frequency range, where most acoustic absorbing materials have little effect on the low-frequency noises. [7][8][9][10] Lastly, the unsteady flows are characterized by in-and-out states of the compressor unit, and the pressure conditions can be complex in all chambers during different running conditions. 11,12 Thus, the main aim of this paper is to design effective control strategies to attenuate the clunking noise levels during the switching process of operation.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon-fiber-reinforced polymer composites (CFRPs) have been increasingly used during the past decades due to their potential for significant weight saving [ 1 , 2 , 3 ]. Historically, thermoset resins have been used as matrix for CFRPs [ 4 , 5 , 6 ], but the requirements for thermoplastic matrix have been elevated during the past decade [ 7 , 8 , 9 ]. Compared with thermosets, thermoplastics are inherently tough [ 10 , 11 , 12 ], recyclable, and have an unlimited shelf life [ 13 ].…”
Section: Introductionmentioning
confidence: 99%